2004
DOI: 10.1097/01.mlg.0000149450.37640.db
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Growth Factors for Aging Voice

Abstract: The present results suggest that growth factors, especially basic fibroblast growth factor, may have therapeutic potential in restoration of aged vocal fold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
80
0
11

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(101 citation statements)
references
References 18 publications
10
80
0
11
Order By: Relevance
“…The stress σ is the applied force F max per unit area A given by (8) The resultant strain ε is given by tangential displacement X max per material thickness H. (9) Shear modulus G is defined as stress per unit strain (10) (11) As DSR = F max / X max then (12) The thickness of the adult human vocal fold lamina propria is typically 1 mm [26], which is the figure used for H. The area of attachment is obtained by measuring the bore of the suction attachment, which in this study was 2 mm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stress σ is the applied force F max per unit area A given by (8) The resultant strain ε is given by tangential displacement X max per material thickness H. (9) Shear modulus G is defined as stress per unit strain (10) (11) As DSR = F max / X max then (12) The thickness of the adult human vocal fold lamina propria is typically 1 mm [26], which is the figure used for H. The area of attachment is obtained by measuring the bore of the suction attachment, which in this study was 2 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Current approaches involve the use of hyaluronic acid implants, [2,3,4,5,6] growth factors [7,8,9,10] and mesenchymal stem cells [11,12] to stimulate tissue regeneration and improve wound healing outcomes. The ability to measure the biomechanical properties of the vocal fold without dissecting it out of anatomical context, is an essential pre-requisite to determining the viability of any new tissue repair technique.…”
Section: Introductionmentioning
confidence: 99%
“…Growth factors are capable of regulating fibroblast activity, and the ones that have been shown to regulate the extracellular matrix balance in the vocal cords are the basic fibroblast growth factor (bFGF), which stimulates fibroblast growth and modulates extracellular matrix synthesis, and the hepatocyte growth factor, which plays an important role in tissue regeneration and exerts strong antifibrotic activity for reducing the production of type I collagen in the fibroblasts and increasing the production of hyaluronic acid [16][17][18][19] . The bFGF has been shown to stimulate the synthesis of hyaluronic acid and the growth of 'old' fibroblasts [20] ; on the other hand, the effects of the hepatocyte growth factor vary according to the concentration of the growth factor itself [20] . In 2003, Hirano et al [17][18][19] demonstrated that vocal cord fibroblasts cultivated in vitro were capable of increasing hyaluronic acid synthesis when stimulated by growth factors such as epidermal growth factor, transforming growth factor-␤ 1 , hepatocyte growth factor and bFGF.…”
Section: Discussionmentioning
confidence: 99%
“…Luego de 3 meses de seguimiento, basados en estudios con laringoestroboscopio y parámetros acústicos y aerodinámicos, notaron que mejora la atrofia vocal y los parámetros vocales aerodinámicos y desaparece la apertura glótica 32 . Se han realizado diversos estudios preclínicos en animales con células pluripotenciales endógenas y exógenas, con resultados prometedores, sin embargo la mayoría han sido en lesiones agudas de las cuerdas vocales 33 , por lo que no hay experiencia en el manejo en paciente con presbifonía.…”
Section: Cirugíaunclassified